Pengembangan Perangkat Pembelajaran Fisika Berorientasi Pada Model Problem Based Learning Di SMPN 24 Banjarmasin - Suriazdin, Syamsul Alam; Zainuddin, Zainuddin; Mahardika, Andi Ichsan (Universitas Lambung Mangkurat, 2015)
Learning device for teaching materials electrical power and energy in IXE classes SMP 24 Banjarmasin need to be developed using a model of problem-based learning (PBL) to practice the skills of thinking and solving authentic problems that studentsâ learning completeness based on MCC can be achieved. This research aims to descripting the wothiness of electrical power and energy teaching devices that developed oriented on Problem Based Learning model noticed by devices validity, LP carried out, authentic problem solving skills, learning completeness, and studentâs respons. This research included as developmental research refer to development research model according to Dick and Carrey. Research subjects are researcher and 34 students of class IXE SMPN 24 Banjarmasin. Research Instrument that used is validation sheet, LP carries out observation sheet, authentic problem solving skills obsetvation sheet, result study test, and studentâs respons questionnair. Data analyzed by using quantitative descriptive analysis and qualitative descriptive. The Reasearch result indicate that the categories of devices validity is valid, LP carries out is good, authentic problem solving is very good, studentsâ learning completeness are complete, and studentâs responds is good, with the result get concluded that the suitable of learning devices for electrical power adn energy oriented to problem based learning model that developed and tested at SMPN 24 Banjarmasin categoried suitable to use.Â Â